Qingzhu Zhonghua renmin gongheguo chengli sanshisi zhounian - zuguo sihua pu xinqu - Jin Jifa,
'Celebrate the 34th anniversary of the founding of the People's Republic of China - the Motherland's Four Modernizations compose a new hymn'. Printno. 8081.13624.